Gridded composite high resolution bathymetry of a subset from the Calabrian Arc - M112, POS499 - Wintersteller, Paul; dos Santos Ferreira, Christian (MARUM - Center for Marine Environmental Sciences, University Bremen, 2018)
Bathymetry data based on data recorded during M112 between 06.11.2014 and 15.12.2014 and during POS499 between 04.05.2016 and 22.05.2016 in the Mediterranean Sea. The aim of the cruises was to investigate in mud volcanoes of the Calabrian Arc in Italian waters, where 54 potential mud volcanoes have been documented while it remained unclear whether they are still active or not. Therefore, the bathymetric surveys were accompanied with investigations in the water column. Several sound velocity profiles (SVPs) were taken to correct the bathymetry. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de ) as responsible party for bathymetry post-processing and its products. Description of processed data sources at M112: During the cruise M112 the Kongsberg EM122 multibeam echosounder with a nominal sounding frequency of 12 kHz was utilized. 288 beams (and up to 864 soundings in equidistant and dual swath mode) are formed for each ping with a 1°(Tx)/2°(Rx) footprint while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult https://www.km.kongsberg.com/. The EM122 was recording constantly within the permitted areas, either designated to bathymetry surveys or flare imaging-surveys. Responsible person during this cruise / PI: Paul Wintersteller (pwintersteller@marum.de ) and Christian Ferreira (cferreira@marum.de ). Description of processed data sources during POS499: During the RV POSEIDON cruise POS499 the ELAC SB3050 multibeam echo sounder with a nominal sounding frequency of 50 kHz was utilized. 384 beams are formed for each ping while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult http://www.mdsys.co.kr/down/ELAC/SB_3050.pdf. During the POS499 cruise the swath - width has been set to AUTO mode and was commonly observed at around 80°. This given swath ‐ width refers to a coverage of about 1.6 times the water ‐depth and reduces the max. number of beams collected per ping to less than 240. Most of the time the multi‐ping mode has been used with a receiver reception gain value of 45dB. The recorded bathymetry covers in total 880 km and the mapped area is based on the bathymetry results from the M111 & M112 cruises. Responsible person for hydroacoustics during this cruise / PI: Paul Wintersteller (pwintersteller@marum.de ) Description of data processing : Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de ). The open source software MB-system suite (Caress, D.W., and D.N. Chayes, MB-System Version 5, Open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. Tidal changes in the Mediterranean Sea are up to max. 1m. CTD measurements were taken during the M112 and POS499 cruise, and these were sufficient to represent the changes in the sound velocity throughout the study area. Further pitch and heave corrections were not applied for the M112 and POS499 data though a roll off-set of -0.46° was applied for the POS499 data (mbset). Bathymetric data has been manually cleaned for existing artefacts with mbeditviz. NetCDF (GMT) grids of the product and the statistics were created using mbgrid. The currently published merged bathymetric grids of the cruise have a resolution of 30 m. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de).